Semiotic Analysis of Charles Pierce on The Short Story “Cat in The Rain” By Ernest Hemingway - Soegiarto, Heryono; Darmawan; Syamsurrijal (CV Insan Kreasi Media, 2025)
This study analyzes Ernest Hemingway’s short story Cat in the Rain through the lens of Charles Sanders Peirce’s semiotic theory, with a particular focus on the concept of the icon. Peirce’s semiotics is based on three key elements: the sign, the object, and the interpretant, which together construct meaning. Among these, the icon is a sign that resembles or directly represents its referent. This research aims to identify and interpret the various iconic signs present in Hemingway’s narrative, shedding light on their role in shaping the story’s deeper meanings. Through a close reading of Cat in the Rain, several iconic markers emerge, contributing to the story’s symbolism and thematic depth. The cat itself, as an icon, represents unfulfilled desires, loneliness, and emotional longing, mirroring the protagonist’s inner struggles. Other significant icons, such as the rain and the hotel setting, reinforce the atmosphere of isolation and confinement. By analyzing these elements through Peirce’s semiotic framework, this study explores how Hemingway employs iconic signs to communicate complex emotional and psychological states with minimalistic yet powerful language. The findings reveal that the use of icons in Cat in the Rain plays a crucial role in conveying the protagonist’s sense of longing and dissatisfaction. This study contributes to literary semiotics by demonstrating how Peirce’s theory enhances the understanding of Hemingway’s symbolic storytelling techniques. Ultimately, the analysis underscores the effectiveness of iconic representation in literature, offering new insights into the interplay between signs and meaning in Hemingway’s work.